FIRST REPORT OF CO-HARBORING BLEOMYCIN RESISTANCE GENE (bleMBL) AND CARBAPENEMASE RESISTANCE GENE (blaNDM-1) KLEBSIELLA PNEUMONIAE IN IRAQ WITH COMPARISON STUDY AMONG THE SENSITIVITY TEST, THE BD PHOENIX CPO DETECT TEST, AND THE RAPIDEC® CARBA NP TEST - Sarah Ahmed Hasan; Waad Mahmood Raoof; Khaled Khalil Ahmed (Siberian Journal of Life Sciences and Agriculture, 2024)
Two hundred and fifty samples were collected from burn and wound patients between January and July 2023 in Plastic Reconstructive and Burn Surgery Hospital at Sulaymaniyah city/Kurdistan region of Iraq, in addition to the Burn Unit and Wound Care Units of the Azadi Teaching Hospital in Kirkuk, Iraq. We performed a comparison study among (Antibiotic sensitivity test, BD Phoenix CPO detect test and RAPIDEC CARBA NP test), this was the first study of its kind to be performed in Iraq. The findings were supported by molecular detection of two of the most common major carbapenemases in the country, NDM-1 and OXA-48, as well as this study detected five of the recently identified minor/rare carbapenemases worldwide for the first time in Middle East (BKC-1, FRI-1, LMB-1 ,OXA-426, and OXA-198). We recorded five isolates containing chromosomal NDM-1 and OXA-48 genes. The findings indicated that the RAPIDEC CARBA NP test serves as a quick, accurate and sensitive means of detecting all five isolates containing the blaNDM-1 and blaOXA-48 genes. The antibiotic sensitivity test was insufficient in detecting the CPOs while phoenix NMIC-413 AST panel was revealed to be more reliable and accurate in identifying carbapenem resistant isolates in clinical settings than antibiotic sensitivity test and the BD Phoenix CPO detect test report was found to have low detection specificity, further confirmatory tests are required. The current study recorded first report of co-harboring bleomycin resistance gene (bleMBL) and carbapenemase resistance gene (blaNDM-1) Klebsiella pneumoniae in Iraq with accession NO. PP411935. The development of new routine tests for identifying isolates resistant to carbapenem in Iraqi hospitals and other developing countries is very essential. Gram-negative isolates from Iraq that were resistant to carbapenem did not harbor the recently found minor carbapenemase.